First report of Pseudomonas mediterranea causing tomato pith necrosis in Argentina - Alippi, Adriana Mónica (2010)
During the summers of 2007 and 2008 fruiting tomato plants (Solanum lycopersicum cv. Orco) from commercial greenhouses near La Plata, Argentina (35 ºS 57 ºW) showed abundant adventitious root production, apical chlorosis of leaves and a brown discoloration of the stem pith (Fig. 1). These symptoms were similar to those reported by López et al. (1994) and Catara et al. (2002) on tomatoes affected by Pseudomonas corrugata or Pseudomonas mediterranea. Bacteria consistently isolated from stem lesions formed cream-coloured, glistening, convex colonies on sucrose peptone agar (SPA) and were non-fluorescent on King?s medium B (KMB). Four isolates were selected for further study. All were aerobic, Gram-negative rods with PHB inclusions. In LOPAT tests, all induced a hypersensitive response in tobacco plants, were oxidase positive, did not cause soft rot of potato tubers, and were negative for levan and arginine dihydrolase. Colonies developed at 28ºC and 37ºC but not at 41ºC. Additional characterisation was achieved by API 20 NE tests strips(Biomerieux®, Argentina). Reference strains 536.7 (Spain), 592.4 (Spain) and CFBP 10906 (France) of P. mediterranea and strain NCPPB 2445 of P. corrugata were included in all tests for comparison. Further identity was confirmed by PCR, using species-specific primers PC5/1-PC5/2 for P. mediterranea and primers PC1/1-PC1/2 for P. corrugata (Catara et al., 2002). All the strains were identified by the amplification of a 600 bp DNA fragment characteristic of Pseudomonas mediterranea (Fig. 2; Catara et al., 2002). The isolates of P. mediterranea were also differentiated from those of P. corrugata by PCR/RFLP analysis of 16S rDNA gene by using endonuclease AluI (Fig. 3). Pathogenicity was verified on four-week-old tomato plants (cv. Presto) by injecting bacterial suspensions at 107 cfu/ml or sterile distilled water for controls, after which the plants were kept for 72 h in a humid chamber before incubation at 25°C. After 45 days inoculated plants showed necrotic pith symptoms similar to those observed on field-grown plants, whereas no lesions were observed on controls. Pith necrosis caused by P. corrugata and P. viridiflava has been previously reported in Argentina (Alippi et al., 1993 Alippi et al, 2003). This is the first report of a disease caused by P. mediterranea on greenhouse-grown tomatoes in Argentina and South America